Laura Jones Crawford journal - Crawford, Laura Jones, approximately 1837-
Journal (1859 January 1-April 16) primarily concerned with domestic matters but giving occasional references to current events in the Washington area, such as the shooting of Philip Barton Key by Daniel E. Sickles, a ball given for Lord and Lady Napier, and elections in Georgetown. Part of this volume was utilized earlier for lottery accounts and other matters (1838-1839, 1845).
Daughter of the mayor of Georgetown (Washington, D.C.)
Collection material in English.
Keywords: Key, Philip Barton, -- 1818-1859.; Napier, Anne Jane Charlotte Lockwood, -- Lady; Napier, Francis Napier, -- Baron, -- 1819-1898.; Sickles, Daniel Edgar, -- 1825-1914.; Georgetown (Washington, D.C.) -- Politics and government; Georgetown (Washington, D.C.) -- Social life and customs